Orientation of the magnetic moments in perpendicular anisotropic thin films by hall effect - Nguyen, Hong Thi Minh; Nguyen, Duc Huy; N.H, Sinh; Vu, Thuc Nguyen (VNU Journal of Science: Mathematics - Physics; Vol 20 No 3AP, 2017)
Abstracts